An investigation on the application of time-frequency signal analysis for HF data communication signals - Ahmad Zuri Sha'ameri (Skudai : Universiti Teknologi Malaysia, 2000)
Thesis (Doctor of Philosophy) - Universiti Teknologi Malaysia, 2000